Rancang Bangun Oven Pengasapan Ikan Asap Menggunakan Metode Rotary - Novison, Roni; Nugraha, Nurcahya; Akhyan, Amnur (Jurnal Teknik Mesin, 2024)
Smoked fish has a high economic potential to be used as a business or to cook household food, so it is appropriate if this opportunity is developed by the community. One of the areas producing smoked fish is Kampar Regency. Based on the results of a survey conducted in the area of ​​the Koto Village Mosque (Kampung Patin) Kampar Regency, it was still found that the processing process carried out by the local community still uses traditional equipment, such as using rambutan wood as fuel and a fire stove placed outside the house during the smoking process, so that the temperature of the furnace combustion cannot be controlled properly and the quality of the resulting product is not good for large-scale production, because smoke and ash often stick to the fish meat, and the fish is not evenly cooked. One way that can be done to facilitate the process of making smoked fish is to create a smoking room that can inhibit heat energy by using a rotating system that can rotate. Small holes are also made in the iron pipe in the smoking room as a flow of smoke which aims to make the fish evenly cooked. The smoking process in the oven uses a rotating system or the fish will be rotated in the oven. This study was conducted in order to produce average smoking and this study includes the quality of appearance, odor quality, taste quality, texture quality, mushroom quality, and mucus. The smoking was carried out for 2 hours, 3 hours and 4 hours. The smoking oven was designed to have a smoke chamber capacity of 6 kg with a division of 1 kg / rack. The main part of the smoking oven machine is divided into two main parts including the smoke chamber and the combustion chamber. The smoke chamber has dimensions of 75 cm long, 50 cm wide and 120 cm high while the combustion chamber has dimensions of 100 cm long, 80 cm wide and 50 cm high. The best fish smoking results were obtained at a smoking time of 3 hours with an average fish shrinkage of 42.12%. This can be seen from the level of color and weight shrinkage.